Single Mother Families in Lithuania: Demographic and Socio-economic Characteristics - Stankūnienė, Vlada; Baublytė, Marė; Maslauskaitė, Aušra (Sociologija. Mintis ir veiksmas, 2017)
The aim of this article is to reveal the socio-demographic and socio-economic characteristics of single mother families in Lithuania. The article is based on the 2011 Census data and presents the results of the individual level data analysis. Our findings prove that single parent families constitute a substantial share of all families with underage children in Lithuania. Nearly one third of all underage children live in single parent families and this places Lithuania in the forefront of other EU countries. Along with more traditional paths leading towards the single mother families, including divorce and widowhood, there is a significant share of married mothers living without a partner. Our results also highlight the economic vulnerability of lower-educated, rural-residing, non-married mothers, as almost half of them are depending on a formal social support system.
Keywords: single mother families; family well-being; socio-economic and socio-demographic characteristics